Efecto de Bacillus subtilis en el desarrollo de Phytophthora capsici L. en Capsicum annuum L. var. Longum - Blas Alfaro, Luz Del Solar (2019)
The objective of the present investigation was to determine the effect of Bacillus subtilis on the development of Phytophthora capsici L. in Capsicum annuum L. var. Longum The individual and combined effect of two strains of B. subtilis (RP-18 and RP-1) was evaluated by applying 50 ml of the bacterial suspension of 109 cfu / ml to the bare root transplant and to the soil after transplantation. Twenty days later, 20 ml of a concentration of 105 zoospores / ml was applied. Two treatments were included, one without antagonist and one single pathogen. The treatments were distributed using a completely randomized design with eight treatments and five repetitions. The parameters evaluated were the antagonistic effect "in vitro", plant height, incidence and severity of P. capsici. SPSS version 24, and Dunnet's comparisons test. Strains of Bacillus subtilis "in vivo" inhibit the mycelial growth of Phytophthora capsici, highlighting the strain RP-18 with greater area of inhibition. The treatments with Bacillus subtilis are applied to the transplant in a bare root and after the transplant, there is a severity between 85% and 100%; likewise, the characteristic symptoms of P. capsici are published after 7 days of inoculation and the death of the plants occur 17 to 21 days after inoculation.